Self-Management Programs of Fatigue Syndrome in Children and Adolescents Living with Chronic Conditions: A Systematic Review - Vincentia Exandy Salvera Arnoldy; Allenidekania Allenidekania; Siti Chodidjah; Etty Rekawati (Indonesian Journal of Global Health Research, 2025)
Chronic fatigue syndrome is a debilitating illness of unknown cause that affects physical, psychological, emotional, and social aspects of life, manifesting in poor physical stamina, reduced social interaction, and depression. Self-management programs involve the deliberate practice of specific tasks, activities, and behaviors aimed at managing the medical, psychosocial, and daily life impacts of chronic illness. These programs include strategies such as symptom monitoring, adherence to treatment plans, and maintaining healthy practices. Aim to evaluate the effectiveness of self-management programs in reducing fatigue so as to improve quality of life. In a study utilizing the PICO search strategy related to self-management activities for reducing fatigue, 396 articles were found in the Cochrane, PubMed, Medline, Taylor & Francis, ProQuest, ScienceDirect, and Sage databases between 2020-2024; four articles meeting the inclusion criteria were analyzed in depth using quality assessment tools such as PRISMA. The study protocol was registered in the Prospective Register of Systematic Reviews (PROSPERO) with the following registration number: CRD42024622785. Based on the literature search was conducted without restrictions on the start year, including publications up to 2024.", 415 articles were identified, 19 duplicate articles were selected, until 5 eligible articles were obtained based on the selection of design, participant, intervention, and outcome This review concludes that self-management, such as lifestyle advice, web-based programs, and physical activity, is effective in reducing fatigue, and to achieve better quality of life and fatigue reduction outcomes, tailored to patient needs and conditions needed to be strengthened.